Forest Biosecurity Systems and Processes: An Indian Perspective - Gupta, Kavita; Sankaran, K. V. (Frontiers in Forests and Global Change, 2021)
Biological invasions continue unabated across the globe despite all efforts to manage the problem by implementing biosecurity regulations and associated management methods. In this context, this paper reviews the plant biosecurity legislation applicable to agriculture and forestry sectors in India to prevent/manage invasions, with the objective of identifying limitations in the legislation or lapses in implementing it and propose corrective measures. The legislation can be improved by: (1) revising and updating the Destructive Insects and Pests Act (1914) and Plant Quarantine Order 2003 and (2) establishing a National Sanitary and Phytosanitary Database Center to promote exchange of information. Establishing more plant quarantine stations with state-of-the-art facilities and a Biosecurity and Trade Unit may support implementation of legislation. Some of main gaps in information and research in biosecurity are identified. The plant biosecurity legislation, though meant to be common, mainly addresses the agriculture sector; its application in the forestry context is currently scarce. Hence, it is suggested that India may enact forest biosecurity scrupulously especially in the context of introducing the REDD + strategy and a Forest Certification Scheme. It is proposed that an integrated pest management (IPM) system involving e-pest surveillance, establishment of pest-free areas and use of biocontrol may help tackle emerging pest threats. The use of new technologies for remote sensing and detection and mapping of vegetation may help bio-surveillance, forecasting, and monitoring of pests. However, successful implementation of all management options demands formation of an exclusive national policy to manage invasive alien species and an action plan governed by a single agency. To realize the plant biosecurity goals, India may also strengthen regional cooperation to: (1) harmonize regulations for sanitary/phytosanitary and plant quarantine/biosafety measures and (2) use a common pest risk analysis (PRA) for unknown pests in the region. Capacity-building of officials to identify risky goods and verify conformity with Import Health Standards is raised. Also, raising awareness on biosecurity among all stakeholders and involving them in implementing the legislation would be helpful. The proposed National Agricultural Biosecurity System and the Agricultural Biosecurity Bill currently considered by the Indian Parliament is expected to address the inadequacies.